Introducing a New Grade 8 Curriculum in Children’s Rights - Covell, Katherine; O'Leary, Johnna L.; Howe, R. Brian (Alberta Journal of Educational Research, 2002)
Existing research indicates that the effective implementation of new curricula depends on several variables including teachers' agreement with the goals of a new program, its impact on workload, and opportunities for professional development. The purpose of this research was to assess how far 31 grade 8 teachers implemented a new children s rights curriculum, whether the implementation of the curriculum changed their and their students' attitudes about children's rights, and to identify factors that encouraged implementation. Major findings were as follows: Workload, defined in terms of years of experience and class size, was predictive of curriculum use. The more teachers used the curriculum, the higher they rated it and the more they expressed attitudes supportive of children's rights. Students' support for the rights of adults, including ethnocultural minorities and those with disabilities, was positively related to their teachers' support for children's rights.